COMPUTERS IN THE SCIENCE CURRICULUM—SOME CONCRETE APPLICATIONS IN THE PHYSICAL SCIENCES. - Lunetta, Vincent N.; Dyrli, Odvard Egil (Science Education)
The article discusses the use of computers in instruction and in educational data processing in schools in the U.S. Computers are said to be a potential solution to many of the problems besetting public education. In such applications, the computer will enhance the understanding of the learning process. The first applications of electronic computers were the processing of data for mathematical and scientific research. The computer has begun to assume a role in the classroom. Students are introduced to data processing and to computer programming in a number of secondary schools. When students have received basic training in programming, they are better equipped to solve a broader range of meaningful science problems which are seldom introduced in temporary courses.